Kekerasan terhadap Anak dalam Panti Sosial Asuhan Anak - Ismet Firdaus (Social Welfare Study Program, 2012)
Violence against children in Indonesia continues to increase. Many cases of violence, one of them, as happened at the childcare institution (orphanage). Forms of violence and crime are physical, psychological, sexual, and neglect. Results of the study conducted by Ministry of Social Affairs, UNICEF, and Save the Children showed that the factors that support the physical and psychological violence to the children are associated with the method in educating and disciplining children. Often used physical force or by means of humiliating and degrading treatment of children. Ironically, the staff and caregivers view it as an important part of their role in doing the job. Keywords: kekerasan, kekerasan terhadap anak, kejahatan kekerasan.